TO WHAT EXTENT CAN PROVIDING SCAFFOLDING IN ZPD HELP IN DEVELOPING SLA OF ENGLISH LANGUAGE LEARNERS? - Asri Purnamasari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2017)
ABSTRACTAs learners face difficulties in acquiring Second Language Acquisition (SLA) where English is used as a foreign language, in this writing she will analyse the writer practice as a teacher in a secondary school in Indonesia through the lens of Vygotskian Socio-Cultural Theory – Zone of Proximal Development (ZPD). She illustrate how ongoing support through cooperative learning which promoted teamwork and dialogue among peers could help learners understand the concept of using procedure text. Although social interaction involvement has been controversial, the learning process, through which support or scaffolding is provided in learners’ ZPD, can have a positive effect on language development.Key Words: Scaffolding, ZPD, SLA, EFL, Cooperative Learning, Socio-cultural Theory ABSTRAKSebagaimana para siswa menghadapi kesulitan dalam mencapai Second Language Acquisition (SLA) di mana Bahasa Inggris digunakan sebagai Bahasa asing, dalam tulisan ini saya akan menganalisa pengajaran pada sekolah menengah di Indonesia berdasarkan Vygotskian Socio-Cultural Theory – Zone of Proximal Development (ZPD). Dalam tulisan ini akan terjabarkan bagaimana dukungan terus-menerus (scaffolding) melalui cooperative learning yang menggunakan teamwork dan dialog antar siswa dapat membantu mereka mengerti konsep dari penggunaan procedure text. Meskipun penerapan interaksi sosial masih menjadi konstroversi dalam proses pembelajaran, namun scaffolding yang selalu dberikan pada ZPD siswa terbukti dapat memberikan dampak positif dalam perkembangan bahasa.Kata Kunci: Scaffolding, ZPD, SLA, EFL, Pembelajaran Kooperatif, Socio-cultural Theory